2007
DOI: 10.4028/www.scientific.net/amr.26-28.511
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Post Weld Heat Treatment on Mechanical Properties of Friction-Welded Alloy 718 and SNCRW Stainless Steel

Abstract: The effect of post weld heat treatment on mechanical properties of friction welded Alloy 718 and SNCRW was investigated. Friction welding tests were carried out at a constant rotation speed and pressure. Optimum friction condition was found to be the friction pressure of 25kg/cm2, friction time of 40sec, upset pressure of 80 kg/cm2, and dwell time of 5sec. After friction welding tests, post weld heat treatments were performed in the temperature range of 500-900°C for 8hrs in order to investigate the microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Bu et al [16] reported that with increasing friction time, the temperature gradient in the axial direction decreases mainly due to very high energy given in the initial stage and low heat conduction of alloy 718. Kim et al [17] have observed that an aging treatment after friction welding improves hardness and tensile properties of friction welded alloy 718 and SNCrW stainless steel (chemical composition (in wt. %) of SNCrW stainless steel is 0.2 C, 1.4 Si, 19.8 Cr,9.5 Ni and 68.3 Fe).…”
Section: Introductionmentioning
confidence: 99%
“…Bu et al [16] reported that with increasing friction time, the temperature gradient in the axial direction decreases mainly due to very high energy given in the initial stage and low heat conduction of alloy 718. Kim et al [17] have observed that an aging treatment after friction welding improves hardness and tensile properties of friction welded alloy 718 and SNCrW stainless steel (chemical composition (in wt. %) of SNCrW stainless steel is 0.2 C, 1.4 Si, 19.8 Cr,9.5 Ni and 68.3 Fe).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of less flash on the Inconel 718 side may be attributed to the high strength of Inconel 718 at higher temperatures than SS304 during friction welding. On the contrary, SS304 experiences a sharp decrease in flow stress at higher temperatures which softens the alloy enabling it to undergo plastic deformation [29].…”
Section: Microstructural Analysismentioning
confidence: 99%
“…A reduction in impact toughness was observed upon subjecting the joint to a post-weld heat treatment. In a similar study, residual stresses were reduced [29] after subjecting an Inconel 718 – SNCrW friction weld to a post-weld heat treatment. Hence, a post-weld heat treatment could significantly influence the microstructure and the mechanical properties of a dissimilar joint.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the generation of precipitates during PWHT. Kim et al [27] explored the effect of PWHT on the mechanical properties of friction-welded Alloy 718 and SNCrW (in wt% 20 Cr, 10 Ni, 2 W, 1.4 Si, and 66.6 Fe) stainless steel. They found that PWHT samples resulted in good mechanical properties due to the formation of the γ" phase.…”
Section: Introductionmentioning
confidence: 99%